Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the system of equations:
[tex]\[ \begin{cases} y = -4x \\ y = x^2 - 12 \end{cases} \][/tex]
We need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations simultaneously. Here's a detailed, step-by-step solution:
1. Set the equations equal to each other:
Since [tex]\( y \)[/tex] equals both [tex]\(-4x\)[/tex] and [tex]\( x^2 - 12 \)[/tex], we can set these expressions equal to each other:
[tex]\[ -4x = x^2 - 12 \][/tex]
2. Rearrange the equation to one side to form a quadratic equation:
Move all terms to one side of the equation to set it to zero:
[tex]\[ x^2 + 4x - 12 = 0 \][/tex]
3. Solve the quadratic equation:
To find the values of [tex]\( x \)[/tex], we can solve the quadratic equation using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 4 \)[/tex], and [tex]\( c = -12 \)[/tex].
Calculate the discriminant:
[tex]\[ b^2 - 4ac = 4^2 - 4 \cdot 1 \cdot (-12) = 16 + 48 = 64 \][/tex]
Substitute back into the quadratic formula:
[tex]\[ x = \frac{-4 \pm \sqrt{64}}{2 \cdot 1} = \frac{-4 \pm 8}{2} \][/tex]
So we have two solutions for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-4 + 8}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ x = \frac{-4 - 8}{2} = \frac{-12}{2} = -6 \][/tex]
4. Find the corresponding [tex]\( y \)[/tex]-values:
Substitute each [tex]\( x \)[/tex]-value back into one of the original equations (let’s use [tex]\( y = -4x \)[/tex]) to find the corresponding [tex]\( y \)[/tex]-values.
For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = -4(2) = -8 \][/tex]
For [tex]\( x = -6 \)[/tex]:
[tex]\[ y = -4(-6) = 24 \][/tex]
5. Write the solutions as ordered pairs:
The solutions to the system of equations are the points where the equations intersect. These points are:
[tex]\[ (-6, 24) \quad \text{and} \quad (2, -8) \][/tex]
Therefore, the solution to the system of equations is:
A. [tex]\((-6, 24)\)[/tex] and [tex]\((2, -8)\)[/tex]
[tex]\[ \begin{cases} y = -4x \\ y = x^2 - 12 \end{cases} \][/tex]
We need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations simultaneously. Here's a detailed, step-by-step solution:
1. Set the equations equal to each other:
Since [tex]\( y \)[/tex] equals both [tex]\(-4x\)[/tex] and [tex]\( x^2 - 12 \)[/tex], we can set these expressions equal to each other:
[tex]\[ -4x = x^2 - 12 \][/tex]
2. Rearrange the equation to one side to form a quadratic equation:
Move all terms to one side of the equation to set it to zero:
[tex]\[ x^2 + 4x - 12 = 0 \][/tex]
3. Solve the quadratic equation:
To find the values of [tex]\( x \)[/tex], we can solve the quadratic equation using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 4 \)[/tex], and [tex]\( c = -12 \)[/tex].
Calculate the discriminant:
[tex]\[ b^2 - 4ac = 4^2 - 4 \cdot 1 \cdot (-12) = 16 + 48 = 64 \][/tex]
Substitute back into the quadratic formula:
[tex]\[ x = \frac{-4 \pm \sqrt{64}}{2 \cdot 1} = \frac{-4 \pm 8}{2} \][/tex]
So we have two solutions for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-4 + 8}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ x = \frac{-4 - 8}{2} = \frac{-12}{2} = -6 \][/tex]
4. Find the corresponding [tex]\( y \)[/tex]-values:
Substitute each [tex]\( x \)[/tex]-value back into one of the original equations (let’s use [tex]\( y = -4x \)[/tex]) to find the corresponding [tex]\( y \)[/tex]-values.
For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = -4(2) = -8 \][/tex]
For [tex]\( x = -6 \)[/tex]:
[tex]\[ y = -4(-6) = 24 \][/tex]
5. Write the solutions as ordered pairs:
The solutions to the system of equations are the points where the equations intersect. These points are:
[tex]\[ (-6, 24) \quad \text{and} \quad (2, -8) \][/tex]
Therefore, the solution to the system of equations is:
A. [tex]\((-6, 24)\)[/tex] and [tex]\((2, -8)\)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.